TYPOLOGY OF PERSONAL TRAITS OF OFFICERS INVOLVED IN THE TRAINING OF CADETS AT HIGHER MILITARY EDUCATIONAL INSTITUTIONS (MILITARY EDUCATIONAL UNITS OF HIGHER EDUCATIONAL INSTITUTIONS) AS THE COMPONENT OF THEIR IMAGE FORMATION - Kravchenko, K.; Hrebeniuk, L.; Belichenko, L. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
The purpose of the article is to highlight some part of the large-scale research on the formation of a positive image of officers involved in the training of cadets at higher military educational institutions (military educational units of higher educational institutions), namely: to present the results of empirical research which effect the determination of typology of their personality traits. In our research we understand typology of personal traits as a set of pronounced and stable psychological characteristics that determine the behavior of the officer during his service. The following categories were determined among the involved officers: officers of the senior level, officers-educators, and officers of the course level of higher military educational institutions (military educational units of higher educational institutions) of the Armed Forces of Ukraine. According to the results of empirical research were defined three most typical personality traits for the officers of senior level and officers-educators, and four of them for the officers of the course level. Personality types of the senior level officers: 1) balanced type (59.43 %); 2) effective (22.42 %); 3) executive or committed (18.15 %). The balanced and effective types encompass the necessary range of personal characteristics that contribute to the formation of a positive image. The executive type lacks management skills. Personality types of the officerseducators: 1) star type (50.14 %); 2) introverted (14.05 %); 3) almost exemplary (11.43 %). Each type of officers-educators has a number of aspects that hinder them from forming a positive image, such as lack of self-will, emotionality, and pedagogical skills, as well as a certain rigidity during classes. Personality types of the course level officers: 1) correct or moral and ethical type (59.39 %); 2) ambitious (14.01 %); 3) infantile (10.78 %); 4) dramatic (9.07 %). Among the identified types of personality traits of course officers, problems in image formation may arise within infantile type. One of the main reasons is the establishment of friendly relations with cadets that affects the service of the latter and does not contribute to the formation of necessary qualities of future officers. That is why this type of officers cannot be a role model for others.
Keywords: personality traits, the image of officers of higher military educational institutions, senior officers, teaching officers, course officers